Reception of A. I. Solzhenitsyn’s Works in Chinese Social, Political, and Cultural Context - Lulu Zhou; A. G. Kovalenko (Научный диалог)
The article analyzes the reception of A. I. Solzhenitsyn in Chinese translations and literary studies. The history of Solzhenitsyn’s texts and research on the Russian writer in the Chinese socio-political and cultural context is studied. It is noted that the perception of Solzhenitsyn in China was not exclusively a literary event, but was closely linked to the Sino-Soviet split in the late 1950s. It is established that the translation and study of Solzhenitsyn’s work in China was asynchronous: translations began in the 1960s, while research started in the mid-1980s. An analysis of the political-cultural background and ideological atmosphere during the translation and study of Solzhenitsyn’s work by Chinese scholars is conducted. The evolution of the perception of the writer’s personality and work is shown to have shifted from negative to positive, which is attributed to a change in literary criticism approach from vulgar sociological critique to artistic text critique. It is revealed that with the disappearance of ideological pressure, Chinese academic circles began to differentiate between Solzhenitsyn as a writer and Solzhenitsyn as a political figure. This division has contributed to a more adequate understanding of Solzhenitsyn and his literary legacy. Currently, Chinese scholars highly value Solzhenitsyn’s literary legacy and objectively and rationally relate to his political position and statements.